Quantitative Assessment of Luliconazole and Gallic Acid Simultaneously in Formulated Emulgel by UV Spectrophotometric Methods - Zanwar, Aarti S. (Asian Journal of Pharmaceutics (AJP), 2022)
Introduction: Three new UV spectrophotometric approaches specifically, simultaneous equation (SME), absorbance ratio (ASR), and first derivative (zero crossing) spectroscopic techniques were developed and validated for simultaneous estimation of luliconazole (LCZ) and gallic acid (GLA) in emulgel formulation which were simple, sensitive, precise, and accurate. Materials and Methods: In SME method, absorbance was measured at 299 and 259 nm for both the drugs. LCZ and GLA were estimated at 299 and 266 nm in the ASR method. First derivative (zero crossing) method depended on the change of UV spectra in to first derivative spectra followed by measurement of first derivative signal at 249 and 259 nm for LCZ and GLA, respectively, using 4 nm as wavelength interval (Δλ) and 4 as scaling factor. Developed methods were validated according to ICH guidelines including parameters, namely, specificity, linearity, range, precision and accuracy, limit of detection, and limit of quantification. Results and Discussion: All three techniques showed direct relation of absorbance in the concentration range of 1-30 μg/ml for both the drugs. Good repeatability, low intra and inter-day variability, indicate that precise agreement within the value. Recovery studies for both drugs ranged from 97 to 102 percent, recommending that the methods are effective. Results of method validation parameters such as linearity and range, precision, and accuracy adhere to ICH guideline acceptable limit. Conclusion: All the developed methods were found to be quick, profoundly accurate and financially effective; and henceforth can be valuable for simultaneous estimation of LCZ and GLA in emulgel formulation for routine quality control analysis.